From shape to cells: mouse models reveal mechanisms altering palate development in Apert syndrome - Neus Martínez-Abadías; Greg Holmes; Talia Pankratz; Yingli Wang; Xueyan Zhou; Ethylin Wang Jabs; Joan T. Richtsmeier (The Company of Biologists, 2013)
SUMMARY Apert syndrome is a congenital disorder characterized by severe skull malformations and caused by one of two missense mutations, S252W and P253R, on fibroblast growth factor receptor 2 (FGFR2). The molecular bases underlying differential Apert syndrome phenotypes are still poorly understood and it is unclear why cleft palate is more frequent in patients carrying the S252W mutation. Taking advantage of Apert syndrome mouse models, we performed a novel combination of morphometric, histological and immunohistochemical analyses to precisely quantify distinct palatal phenotypes in Fgfr2+/S252W and Fgfr2+/P253R mice. We localized regions of differentially altered FGF signaling and assessed local cell patterns to establish a baseline for understanding the differential effects of these two Fgfr2 mutations. Palatal suture scoring and comparative 3D shape analysis from high resolution μCT images of 120 newborn mouse skulls showed that Fgfr2+/S252W mice display relatively more severe palate dysmorphologies, with contracted and more separated palatal shelves, a greater tendency to fuse the maxillary-palatine sutures and aberrant development of the inter-premaxillary suture. These palatal defects are associated with suture-specific patterns of abnormal cellular proliferation, differentiation and apoptosis. The posterior region of the developing palate emerges as a potential target for therapeutic strategies in clinical management of cleft palate in Apert syndrome patients.